The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura) - Galil, Bella S. (Zenodo, 2007)
Galil, Bella S. (2007): The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). Zoosystema 29 (3): 555-563, DOI: http://doi.org/10.5281/zenodo.4689950 : {"references": ["AHYONG S. T. & GALIL B. S. 2006. - Polychelidae from the southern and western Pacific (Decapoda, Polychelida). Zoosystema 28 (3): 757-767.", "BLABER S. J. M. & MILTON D. A. 1990. - Species composition, community structure and zoogeography of fishes of mangrove estuaries in the Solomon Islands. Marine Biology 105: 259-267.", "BRUCE A. J. 1980. - Some Pontoniine shrimps from the Solomon Islands. Micronesica 16 (2): 261-269.", "CASTRO P. 2005. - Crabs of the subfamily Ethusinae Guinot, 1977 (Crustacea, Decapoda, Brachyura, Dorippidae) of the Indo-West Pacific region. Zoosystema 27 (3): 499-600.", "CHALLIS D. A. 1969. - An ecological account of the marine interstitial opisthobranchs of the British Solomon Islands Protectorate. PhilosophicalTransactions of the Royal Society B 255: 527-539.", "CHEN H. 1989. - Leucosiidae (Crustacea, Brachyura), in FOREST J. (ed.), Resultats des campagnes MUS- ORSTOM, volume 5. Memoires du Museum national d'Histoire naturelle ser. A, 144: 181-263.", "CHEN H. & SUN H. 2002. - Brachyura: marine primitive crabs, in Fauna Sinica Invertebrata: Arthropoda: Crustacea 30. Science Press, Beijing, xiii + 597 p., 237 figs, 6 pls.", "CLEVA R. & CROSNIER A. 2006. - Heterocarpus tenuidentatus a new species of shrimp from the Solomon Islands (Crustacea, Decapoda, Caridea, Pandalidae). Zootaxa 1200: 61-68.", "CROSNIER A. 1997. - Une nouvelle espece de Mursia de Nouvelle-Caledonie (Crustacea, Decapoda, Brachyura, Calappidae). Zoosystema 19 (1): 151-158.", "GALIL B. S. 1997. - A revision of the Indo-Pacific species of Calappa Weber, 1795 (Crustacea: Brachyura: Calappidae), in CROSNIER A. (ed.), Resultats des campagnes MUSORSTOM, volume 18. Memoires du Museum national d'Histoire naturelle 176: 217-335.", "GALIL B. S. 2001a. - A new genus and species of leucosiid crabs (Crustacea, Decapoda, Brachyura) from the Indo-Pacific Ocean. Zoosystema 23 (1): 65-75.", "GALIL B. S. 2001b. - A revision of the genus Arcania Leach, 1817 (Brachyura, Decapoda: Leucosioidea). Zoologische Mededelingen 75 (11): 169-206.", "GALIL B. S. 2001c. - A revision of Myra Leach, 1817 (Brachyura, Decapoda: Leucosioidea). Zoologische Mededelingen 75 (24): 409-446.", "GALIL B. S. 2003a. - Four new genera of leucosiid crabs (Crustacea: Brachyura: Leucosiidae) for three new species and nine species previously in the genus Randallia Stimpson, 1857, with a redescription of the type species, R. ornata (Randall, 1939). Proceedings of the Biological Society of Washington 116 (2): 395-422.", "GALIL B. S. 2003b. - Contribution to the knowledge of Leucosiidae II. Euclosia gen. nov. (Crustacea: Brachyura). Zoologische Mededelingen 77 (20): 331- 347.", "GALIL B. S. & CLARK P. F. 1994. - A revision of the genus Matuta Weber, 1795 (Crustacea: Brachyura: Calappidae). Zoologische Verhandelingen 294: 1-55.", "GIBBS P. E. 1971. - The polychaete fauna of the Solomon Islands. Bulletin of the British Museum (Natural History) 21: 99-211.", "GOGGIN L. 2004. - Solomon Islands: a marine life survey. Tropical Conservancy 5 (4): 8-11.", "MACPHERSON E. 2003. - Some lithodid crabs (Crustacea: Decapoda: Lithodidae) from the Solomon Islands (SW Pacific Ocean), with the description of a new species. Scientia Marina 67 (4): 413-418.", "MILLER M. C. 1969. - The habits and habitats of the opisthobranch mollusks of the British Solomon Islands. Philosophical Transactions of the Royal Society B 255: 459-516.", "MORRISEY D. J., COLE R. G., BELL J., LANE I. & READ G.B. 2003. - Low abundances and diversities of benthic faunas of shallow, coastal sediments in the Solomon Islands and their implications for assessing environmental impacts of logging. Pacific Conservation Biology 9: 15-27.", "NG P. K. L., WANG C.-H., HO P.-H. & SHIH H.-T. 2001. - An annotated checklist of brachyuran crabs from Taiwan (Crustacea: Decapoda). National Taiwan Museum Special Publication Series 11: 1-86.", "TAN C. G. S. 1996. - Leucosiidae of the Albatross expedition to the Philippines, 1907-1910 (Crustacea: Brachyura: Decapoda). Journal of Natural History 30: 1021-1058.", "TIRMIZI N. M. & KAZMI Q. B. 1988. - Crustacea: Brachyura (Dromiacea, Archaeobrachyura, Oxystomata, Oxyrhyncha). Marine Fauna of Pakistan 4. 1. Institute of Marine Sciences, University of Karachi, BCCI Foundation Chair Publication, Karachi, 244 p.", "WILLIAMS A. B. & CHILD C. A. 1988. - Comparison of some genera and species of box crabs (Brachyura: Calappidae), southwestern north Atlantic, with description of a new genus and species. Fishery Bulletin 87: 105-121.", "WOLFF T. 1969. - The fauna of Rennell and Bellona, Solomon Islands. Philosophical Transactions of the Royal Society B 255: 321-343."]}